Princípio Federativo e Reforma Tributária - Krasovesky, Carolina Gomes do Nascimento (2024)
The present work aims to analyze Tax Reform and the Federative Principle. The Tax Reform, which changes the competence of federated entities, as well as administrative, political, legal and financial autonomy, tends to abolish the federative form of State. The Federative Principle is considered an immutable clause and, according to the 1988 Federal Constitution, any reform aimed at abolishing the federative form of State is riddled with unconstitutionality. The essential clauses are enshrined in the Federal Constitution, in its article 60 § 4, in which the Original Constituent Power limits the Derived Constituent Power, so that the Federal Constitution, in its essential core, is not reformed by constitutional amendment. However, who will be responsible for determining the constitutionality or unconstitutionality of the reform and violation of the Federative Principle is the Judiciary, the final and definitive interpreter of any rule that violates the Federal Constitution. We will begin this work by addressing the legal system, composed of norms, principles and legal rules, as well as the meaning of principles, legal-constitutional principles, and their interpretation. The origin of the Federal State, its characteristics, the Brazilian Federal State and its federative entities, with their respective autonomies, and the importance of the federative principle as an essential clause, in addition to tax competence, its characteristics and limitations. We will address Tax Reform from the original text, Proposed Constitutional Amendment nº 45/2019, to the promulgation of Constitutional Amendment nº 132/2023, which changes the National Tax System, focusing on changes in competences. And we conclude that the transfer of state and municipal competences recarding the taxation of ICMS under state competence and ISS under municipal competence to IBS under competence shared between States, Municipalities and District to be exercised in an integrated manner by the Tax Management Committee on Goods and Services, modifies state and municipal autonomies and shows a tendency to abolish the federative form of State, principle and immutable clause. However, the constitutionality or unconstitutionality of the Tax Reform, in terms of violation of the Federal State, will depend on a decision by the Federal Supreme Court, if the issue is taken to the Greater Court